CITRA DIRI SUNDA SEBAGAI FONDASI PEMBANGUNAN MENTAL MANUSIA JAWA BARAT DI ERA SOCIETY 5.0 - Gilar Gandana (LPPM Universitas Perjuangan Tasikmalaya, 2021)
The crystallization of values ​​that need to be built in the Sundanese culture are penance hone, penance, and penance. The form of anxiety that arises in this study is the mental development process of humans holding Sundanese culture in the future. Sundanese culture is currently participating in the industrial revolution 4.0 era. Various efforts must be made to maintain and even improve the human mentality of Sundanese culture owners so that they remain and are able to live together, bring, and elevate the dignity of Sundanese culture to the world surface in the era of society 5.0. One of the logical and realistic efforts to deal with this anxiety is through the application of pedagogic concepts through a Sundanese cultural approach as a jack for inculcating a Sundanese self-image in children in the world of children's education in West Java province in order to build a human mentality that is ready and worthy of living in the West Java province. era of society 5.0. Key Word: Self Image, Mental, Sundanese Culture, Era Society 5.0